Are small business owners more successful in avoiding taxes: Evidence from Sweden - Åsa Hansson (Lund University, School of Economics and Management, Department of Economics, 2009)
It is commonly argued that high tax rates motivate individuals to start a business as it is easier to avoid and evade taxes if self-employed compared to employed. If this is the case we would expect small business owners to be more responsive to tax rate changes than employees. This study investigates how responsive existing small business owners are to tax rate changes by estimating the elasticities of taxable income, gross income and reported income from business ventures for small business owners and contrast them to corresponding elasticities for employees. This is done by using a particularly rich Swedish data set and the 1990/91 Swedish tax reform as a "natural experiment". I find that small business owners' taxable income is about twice as responsive to tax rate changes than employees'. When it comes to reported income from business ventures the difference between small business owners and employees are even greater. For gross disposable income, however, business owners are not more responsive. This is consistent with the hypothesis that small business owners have greater means to shift income between different income sources in order to avoid taxation.
Keywords: H24; H26; J24; 330; Taxable income elasticities; tax avoidance